PENDIDIKAN MULTIKULTURAL DALAM AL-QUR’AN - Febri Janatul Yuda; Yesi Ulandari; Charles (CV. ADIBA AISHA AMIRA, 2025)
Religious plurality anywhere in the world, except in certain places, is a reality that cannot be denied. Contacts between communities of different cultures are increasing. Indonesia is known as a pluralistic society, this can be seen from the existing social reality. Evidence of its diversity can also be proven through the motto of Bhineka Tunggal Ika, multicultural education is a solution to calm and a solution in education in Indonesia. This work is compiled based on data in the form of a 'library research' literature study with a philological- phenomenological approach. From this study it was found that the values of multicultural education can be found in the Qur'an and Hadith and can be implemented by implementing several things such as building an inclusive religious paradigm in the school environment, respecting language diversity in schools, building a sensitive attitude gender in schools, building a critical understanding of social differences, building an attitude of anti- ethnic discrimination, respecting differences in abilities and respect age differences.